PENGARUH STRUKTUR MODAL TERHADAP HARGA SAHAM STUDI PADA PT ANEKA TAMBANG, Tbk - rosita, yeti (Sekolah Tinggi Ilmu Ekonomi Yasa Anggana Garut, 2024)
The aim of this research is to determine the extent of the development of capital structure and stock prices, as well as the influence of capital structure on stock prices. The research method employed is a quantitative research method with an associative causal relationship approach. The data analysis techniques used include correlation analysis, determination analysis, and regression analysis. Based on the data analysis results, the development of capital structure and stock prices shows fluctuations, experiencing increases and decreases each year. The correlation analysis yields a result of -0.413 or 41.3%, indicating a moderate relationship between capital structure and stock prices. The determination analysis result is 0.170 or 17.0%, with the remaining 83% influenced by other factors not examined in this study. The regression analysis result is Y = 18.683 + -20.535 X, meaning that for every 1% increase in the X variable (capital structure), the Y variable (stock prices) decreases by -20.535, or conversely, if there is a 1% decrease in the X variable (capital structure), the Y variable (stock prices) increases, and when the X variable (capital structure) is 0, the Y variable (stock prices) is 18.683. Companies utilizing external capital structure should reconsider borrowing funds externally, or if the company borrows externally, managers should minimize the risks associated with debt usage to achieve an optimal capital structure.